Reliability and validity of the brief dimensional apathy scale. (11th February 2020) - Radakovic, Ratko; Gray, Debbie; Dudley, Kaitlin; Mioshi, Eneida; Dick, David; Melchiorre, Giulia; Gordon, Harry; Newton, Judith; Colville, Shuna; Pal, Suvankar; Chandran, Siddharthan; Abrahams, Sharon
Abstract: Objective: Apathy is composed of different demotivational subtypes measurable by the dimensional apathy scale (DAS) and can be quickly assessed using the brief DAS (b-DAS). The aim was to determine the reliability and validity of the b-DAS. Methods: 53 amyotrophic lateral sclerosis (ALS) patients and 53 of their informants were recruited. Informants completed the b-DAS, the original informant/carer-rated DAS and behavioral interview about the patients (i.e., presence of behaviors such as apathy/inertia, loss of sympathy/empathy). Patients completed measures of depression, anxiety, emotional lability, cognitive functioning, and functional disability measures. Results: The b-DAS showed good internal consistency, excellent test–retest reliability, significant positive correlation with the original DAS, and no significant correlations with depression, anxiety, emotional lability, cognitive functioning or functional disability measures. Semi-structured behavior interview showed patients with apathy/inertia had significantly higher b-DAS subscale scores and patients with loss of sympathy/empathy had significantly higher emotional apathy scores only. Conclusions: The b-DAS is a fast, reliable, and valid instrument for screening apathy subtypes independent of physical disability.